2023
DOI: 10.1007/s11274-023-03634-z
|View full text |Cite
|
Sign up to set email alerts
|

Translational protein RpsE as an alternative target for novel nucleoside analogues to treat MDR Enterobacter cloacae ATCC 13047: network analysis and molecular dynamics study

Abstract: The pathogenic Enterobacter cloacae subsp. cloacae str. ATCC 13047 has contemporarily emerged as a multi-drug resistant strain. To formulate an effective treatment option, alternative therapeutic methods need to be explored. The present study focused on Gene Interaction Network study of 46 antimicrobial resistance genes to reveal the densely interconnecting and functional hub genes in E. cloacae ATCC 13047. The AMR genes were subjected to clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Several studies have reported the role of protein-protein interactions in identification of tumor biomarkers [ 34 ]. The integration of PPIs network analysis with computational bioinformatics techniques can be considered valuable for getting a deep insight into the intricated biochemical interactions occurring among the proteins present in a physiological system and which can give valuable information for designing potential prognostic biomarkers for cervical cancer [ 35 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the role of protein-protein interactions in identification of tumor biomarkers [ 34 ]. The integration of PPIs network analysis with computational bioinformatics techniques can be considered valuable for getting a deep insight into the intricated biochemical interactions occurring among the proteins present in a physiological system and which can give valuable information for designing potential prognostic biomarkers for cervical cancer [ 35 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The local fluctuation in the RMSF was characterized by transient H-bonds formed between MsrD and antibiotics (Figure ). However, the overall average RMSF was fairly low (<1 nm), which depicts considerable stability in protein drug interactions. , Although the interaction dynamics of erythromycin and azithromycin with MsrD is similar (<5% difference in RMSD and RMSF), the latter due to its extended functional groups manages to result in more compaction of the MsrD structure than erythromycin. The same is reflected upon the SASA as compaction reduces the solvent accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…7 A systems biology-based gene interaction network (GIN) comprising curated genes (organism-specific) can help to provide a better understanding of the underlying mechanisms in deregulated biological systems through enrichment and statistical parameters. [8][9][10][11] The need to elucidate the underlying mechanisms is gaining more momentum in complex diseases such as cancer as a result of intricate and extensive investigations. [12][13][14][15][16] The present study applied elaborate systems biology methodology encompassing differential gene expression, GIN and functional enrichment analysis (FEA) to determine the underlying mechanisms promoting metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…A systems biology approach is an interdisciplinary science that deals with complex interactions and considers the collective behavior of the cells as a whole 7 . A systems biology‐based gene interaction network (GIN) comprising curated genes (organism‐specific) can help to provide a better understanding of the underlying mechanisms in deregulated biological systems through enrichment and statistical parameters 8–11 . The need to elucidate the underlying mechanisms is gaining more momentum in complex diseases such as cancer as a result of intricate and extensive investigations 12–16 .…”
Section: Introductionmentioning
confidence: 99%